Theoretical Study of the Absorption Spectrum and the Thermochemistry of the CF3OSO3 Radical - Cobos, Carlos Jorge (2010)
The UV-visible absorption spectrum of the recently reported CF3OSO3 radical has been studied by using the time-dependent generalization of the density functional theory (TDDFT). For this a set of eleven hybrid functionals combined with the 6-311+G(3df) basis set were employed. The main features of the three experimental absorption bands of CF3OSO3 recorded over the 220-530 nm range are well reproduced by the calculations. A dissociation enthalpy for the CF3O-SO3 bond of 19.1 kcal mol-1 is predicted at the BAC-G3MP2//B3LYP/6-311+G(3df) level of theory.